CHANGING IN SOCIETY IN THE CONTEXT OF COVID-19 PANDEMIC CULTURAL PARADIGMAS - BİLİK , Musa (SSD Journal, 2021)
Humans, like all other creatures, have been a part of nature in the process of existence and existence. This is the basic structure of the internal influence between man and nature. Living things that adapt to changes in nature and transformations in the context of space and time have been able to continue their species. A person who falls under the misconception that he has turned the balance of power in nature in his favor with technological developments that began with the Industrial Revolution, saw other living things as an object that should rule, and damaged nature in different dimensions. This has brought many ecosystems on earth to the brink of extinction.The covid-19 epidemic, which threatens human life in many ways within the framework of psychosocial phenomena, has reduced the quality of life of people due to the culture of fear it has created. It also affects some important socio-cultural values that create a society and ensure its unity. The Covid-19 epidemic, which is occurring throughout the world today,affects human history in economic, security, psychological, sociological, literary, religious, political and social aspects, causing significant changes in people’s individual lives and the cultural memory of societies.In this study, psycho-social emotions experienced during the Covid-19 epidemic, socio-cultural situations and behaviors that change and are likely to change in local and universal dimensions are evaluated in the context of culture phenomenon and culture types.